Omnidirectional Image Data-Set for Computer Vision Applications - Berenguel-Baeta, Bruno; Bermudez-Cameo, Jesus; Guerrero, Jose Jesus (Jornada de Jóvenes Investigadores del I3A, 2020)
In this paper we present an image data-set of different omnidirectional systems. The images include full information of colour, depth, instance segmentation and room layout. This dataset aims to help in the training and test of different neural networks and development of computer vision algorithms.